Addressing the rural in situ urbanization (RISU) in the Beijing–Tianjin–Hebei region: Spatio-temporal pattern and driving mechanism. (May 2018) - Zhou, Tao; Jiang, Guanghui; Zhang, Ruijuan; Zheng, Qiuyue; Ma, Wenqiu; Zhao, Qinglei; Li, Yuling
Abstract: Rural in situ urbanization (RISU) indicates that rural settlements transfer into urban land within the original rural settlements area from the perspective of land use. A quantitative study from the perspective of land use can reveal trends of RISU and provide a basis for the promotion of the healthy and rational development of urbanization. Based on the investigation data of land use change of Beijing-Tianjin-Hebei in the period from 2003 through 2015, this paper analyses the spatio-temporal pattern of RISU through the elaboration of RISU and the construction of a rural in situ urbanization index (RISUI), and the driving mechanism of RISU is subsequently discussed. The results showed that RISU fluctuated during the study period in Beijing-Tianjin-Hebei, and its scale between different levels shifted from polarization to balance. RISU displayed a significant spatial agglomeration with the combined influence of siphon and spillover effects in Beijing and Tianjin, and its spatial scope expanded to the periphery with Beijing as the centre. The findings further revealed that RISU was developed under the comprehensive influence of population, economy, social public service and space. To realize the healthy and benign development of urbanization, the government should vigorously promote the RISU of small towns on the basis of resource environmental bearing capacity and the land construction foundation. Meanwhile, urban-rural construction land and the allocation of public service resources should also be arranged. Highlights: Analyse the temporal pattern of rural in situ urbanization Explore the spatial pattern of rural in situ urbanization Discuss the driving mechanism of rural in situ urbanization